2022
DOI: 10.1177/03946320221104548
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen C-protease enhancer protein is a prognostic factor for glioma and promotes glioma development by regulating multiple tumor-related pathways and immune microenvironment

Abstract: Objectives Glioma is a common type of brain tumor with high incidence and mortality rates. Procollagen C-protease enhancer protein (PCOLCE) has been shown to regulate tumor growth and metastasis in several cancers. However, the role of PCOLCE in glioma is unknown. This study aims to assess the association between PCOLCE and prognosis of glioma, and investigated the potential mechanisms. Methods The prognostic value of PCOLCE was determined using data from nine publicly available glioma cohorts. We also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Additionally, our findings showed that high levels of PCOLCE expression may be a predictor of poor outcomes for LGG and GBM patients. The CGGA data also showed that all WHO-grade primary gliomas had a poor prognosis when PCOLCE was over-expressed, consistent with a most recent study [ 35 ]. It has illustrated that PCOLCE actively increases the production of BMP1.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, our findings showed that high levels of PCOLCE expression may be a predictor of poor outcomes for LGG and GBM patients. The CGGA data also showed that all WHO-grade primary gliomas had a poor prognosis when PCOLCE was over-expressed, consistent with a most recent study [ 35 ]. It has illustrated that PCOLCE actively increases the production of BMP1.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research showed that macrophages were more likely to develop into M2 macrophages for the immunosuppressive microenvironment in glioma ( 13 ). Glioma cells can secrete various chemokines to recruit macrophages and regulate the M2 macrophage polarization ( 14 ). Hence, therapy against macrophage polarization and recruitment can be a promising treatment for glioma.…”
Section: Introductionmentioning
confidence: 99%